2016
DOI: 10.2341/15-158-t
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Technique Selection in Class IV Direct Composite Restorations: A Simplified Method

Abstract: Use of the techniques presented here will yield highly esthetic resin composite restorations in minimal time. Although more elaborate composite layering techniques exist and may be used in complex esthetic scenarios, a simplified approach combining two body shades and implementing basic dental anatomy concepts often will deliver highly acceptable esthetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
(8 reference statements)
1
7
0
2
Order By: Relevance
“…In terms of color match and translucency, the results showed that polychromatic natural layering technique (comparator) which is assumed as gold standard [5],was capable of providing a highly aesthetic anterior resin composite restoration with good color match and this was in accordance with [23,40,41] However, according to the current results, it was found that dual shade technique could also provide a highly aesthetic anterior resin composite restoration with good color match, as there was absolute insignificant difference between both groups concerning color match and translucency and this was in accordance with [28].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In terms of color match and translucency, the results showed that polychromatic natural layering technique (comparator) which is assumed as gold standard [5],was capable of providing a highly aesthetic anterior resin composite restoration with good color match and this was in accordance with [23,40,41] However, according to the current results, it was found that dual shade technique could also provide a highly aesthetic anterior resin composite restoration with good color match, as there was absolute insignificant difference between both groups concerning color match and translucency and this was in accordance with [28].…”
Section: Discussionsupporting
confidence: 86%
“…Concerning cavity configuration, the most challenging is the class IV and large class III through and through which have no backing tooth structure. A relatively translucent composite may not be able to mask the dark background of the oral cavity and only one shade may not be able to color match with the remaining tooth structure [28,29] A functional esthetic enamel bevel, was prepared in this study for achieving less marginal microleakage, better adhesion, lower risk of enamel marginal fracture and better transition between composite resin and dental substrate, which inducing higher esthetic pattern [30].…”
Section: Discussionmentioning
confidence: 99%
“…6 O aprimoramento da técnica do condicionamento ácido em esmalte e dentina, com o surgimento de novos sistemas adesivos, aliado ao desenvolvimento das resinas compostas, permitiu a obtenção de restaurações em dentes anteriores mais próximas ao natural, uma vez que os sistemas de resina composta oferecem várias tonalidades que permitem mimetizar as variações de opacidade e translucidez dentária, promovendo a replicação das propriedades ópticas do esmalte e dentina combinados. 2,7 Com isso, a técnica de reanatomização por meio de facetas diretas em resina consiste em um procedimento conservador, exigindo mínimo desgaste da estrutura dental quando comparado ao uso das restaurações indiretas em cerâmica, melhorando assim o comportamento biomecânico dos dentes envolvidos. 4 Diferentes abordagens restauradoras diretas podem ser consideradas para a reanatomização de dentes anteriores, tais como a inserção de resina composta direta à mão livre sobre a superfície dentária, coroas pré-contornadas ou, ainda, o uso de guias de silicone empregadas de modo a orientar o profissional na obtenção de forma e contorno adequados para os dentes a serem restaurados.…”
Section: Introductionunclassified
“…Residual resin material is often removed using diamond or multilaminate burs or abrasive discs. However, identifying the resin material is difficult as it has similar optical properties to tooth enamel . As a consequence, irreversible, iatrogenic, damage, such as grooves and surface irregularities, to the enamel can result from excessive pressure during the removal of adhesive material .…”
Section: Introductionmentioning
confidence: 99%
“…However, identifying the resin material is difficult as it has similar optical properties to tooth enamel. 5 As a consequence, irreversible, iatrogenic, damage, such as grooves and surface irregularities, to the enamel can result from excessive pressure during the removal of adhesive material. 6,7 Similarly, the incomplete removal of adhesive material leads to a rough enamel surface, which favors biofilm accumulation 1 and consequently facilitates the development of white spot lesions.…”
Section: Introductionmentioning
confidence: 99%